The Shikani Optical Stylet as an Alternative to Awake Fiberoptic Intubation in Patients at Risk of Secondary Cervical Spine Injury: A Randomized Controlled Trial. Issue 4 (October 2018) - Mahrous, Rabab S.S.; Ahmed, Aly M.M.
Abstract : Background: Conventional intubation of the trachea and consequent prone positioning of anesthetized patients with cervical spine instability may result in secondary neurological injury. Historically, flexible fiberoptics used to be the chief choice for patients presenting with cervical spine instability surgery with difficult airway. Recently, the rigid optical stylets have shown promise in assisting difficult intubations. Purpose: The aim of the present study was to compare the efficacy of Shikani optical stylet (SOS) with the flexible fiberscope for awake intubation in patients with cervical spine instability. Patients and Methods: In total, 60 adult patients diagnosed with cervical instability or at risk of secondary cervical injury, who were planned for awake intubation and/or self-positioning prone, were registered in this study and were randomly categorized into 2 equal groups (30 patients each), a fiberoptic group and an SOS group, followed by assessment of coughing and gagging during intubation, time to successful intubation, number of attempts for successful intubation, and hemodynamic parameters. Results: As regards time to successful intubation, statistically significant differences were detected between the 2 studied groups, with the fiberoptic group having significantly longer intubation time than the Shikani group, whereas no statistically significant differences were recorded between the 2 groups with regard to the first-attempt success, the mean heart rate value, the mean arterial blood pressure, coughing, and occurrence of complications. Conclusion: This study validates the efficacy of both SOS and flexible fiberoptic bronchoscope for awake oral intubation in patients with cervical spine instability. SOS has been found to be more effective in reducing time to intubation.